2014
DOI: 10.4276/030802214x13887685335544
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapists' Attitudes, Knowledge, and Implementation of Evidence-Based Practice: A Systematic Review of Published Research

Abstract: Evidence-based practice is the procedure whereby clinicians incorporate best research evidence, clinical expertise, and patient values to provide best patient care. Recently, there has been a significant push towards occupational therapists' adoption of evidence-based practice. This systematic review aimed to determine occupational therapists' attitudes, knowledge, and utilization of evidence-based practice. Method: A search of literature published between 2000-12 was conducted in relation to occupational ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
116
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 46 publications
5
116
0
5
Order By: Relevance
“…This very much concurs with the wider accepted view of the current situation 1,6,59 and therapists' views on the barriers to evidence-based practice. [60][61][62][63][64][65][66][67][68] These findings are not unique to the therapy professions investigated in this study, and have been reported across a wide range of health-care professions. [64][65][66] Furthermore, and as other studies report, [61][62][63] the applicability of existing, higher-quality evidence (derived from studies not conducted in routine practice or clinical settings) was questioned.…”
Section: Views About the Need For Researchmentioning
confidence: 69%
See 2 more Smart Citations
“…This very much concurs with the wider accepted view of the current situation 1,6,59 and therapists' views on the barriers to evidence-based practice. [60][61][62][63][64][65][66][67][68] These findings are not unique to the therapy professions investigated in this study, and have been reported across a wide range of health-care professions. [64][65][66] Furthermore, and as other studies report, [61][62][63] the applicability of existing, higher-quality evidence (derived from studies not conducted in routine practice or clinical settings) was questioned.…”
Section: Views About the Need For Researchmentioning
confidence: 69%
“…[60][61][62][63] Perceived challenges of designing and conducting evaluative research Study participants readily identified challenges with evaluating therapy interventions and a minority believed that these were insurmountable. Most regarded them as issues that may themselves need to be researched.…”
Section: Views About the Need For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The most cited barriers are: lack of time, lack of access to research literature, organisational barriers, lack of skills such as searching for literature and critically appraising scientific articles (see also Law & MacDermid, 2014c). Upton, Stephens, Williams and Scurlock-Evans (2014) concluded in their review that the therapists' positive attitudes towards EBP 'do not translate into practice ' (p. 24). Therefore, it is no longer a question if EBP is essential and valued, but rather how to sustainably implement it into clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Technical uncertainty results from having inadequate information to predict effectiveness of the interventions and inform prognosis. For example, often occupational therapy practice has limited research to support interventions (Kuipers & McKenna, 2009;Rassafiani et al, 2008) or therapists may be unaware of the research which is available (Kielhofner, 2005;Upton et al, 2014), both of which could contributing to clinician's technical uncertainty. Personal uncertainty is related to the client-practitioner relationship and understanding the client's goals whereas conceptual uncertainty is linked to applying guidelines, theories and past experiences to current clients (Hall, 2002).…”
Section: Managing Uncertainty In Decision-makingmentioning
confidence: 99%